PENGARUH PERSEPSI MASYARAKAT TERHADAP OBLIGASI DI INDONESIA (Studi Kasus Nasabah PT. Bank Mandiri Tbk Kota Medan) - Teguh Akbar Nugraha Harapah; Kasyful Mahalli (Ekonomi dan Keuangan, 2014)
This research aims to study and analyze the influence of society perception to the obligation in Indonesia (Case study at Customer of PT. Bank Mandiri Tbk Medan city). The society perception is an interpretation based on environment data collected that absorbed by human sense as initiative taking of communication process, while obligation is a medium – long term debenture that can be sell and buy in which the obligation contain promise of the issuer to pay the compensation such as interest (coupon) in certain period.The method of analysis applied in this research is a descriptive analysis and simple linier regression method. This research use the secondary data that collected in documentation study and processed statistically by SPSS program for windonws.The result of research indicates that the society perception has a negative influence and is not significant to the obligation in Indonesia. The value of t-calculated of society perception variable is -1.409 and t-table is 1.980. so t-calculated < t-table (-1.409 < 1.980) and significant value 0.000 < 0.05 because (0.162?0.05). the main reason of customer perception to the obligation is lower because the knowledge (insight) of customer is lower (they only know the obligation as alternative of investment in addition to saving and deposit product and share) and the socialization and promotion must be increased by bank.Keywords : Society perception, Obligation, Bank